Perancangan Mesin Pengaduk Pakan Ternak Type Horizontal Dengan Penggerak Motor Diesel 5 Pk - Akmal Indra; Rahmat Fajrul; Mahfuddin; M Abdullah; Budi Hidayat (ABEC Indonesia, 2022)
Palm fronds resulting from the pruning process can be used as organic fertilizer and animal feed.Communities in Bengkalis Regency, especially in Pinggir District, are still constrained in the processing of palmmidrib to be used as animal feed, especially in the process of mixing or stirring. The purpose of this research is todesign and manufacture a horizontal type animal feed mixer machine and to test the performance of the machine.This research activity will later conduct machine performance trials at research partners and conduct training onthe use of machines and hand over machines to research partners to be utilized or used in the process of mixinganimal feed.